Antimicrobial activity of açaí against Listeria innocua. (July 2015) - Belda-Galbis, Clara Miracle; Jiménez-Carretón, Antonio; Pina-Pérez, María Consuelo; Martínez, Antonio; Rodrigo, Dolores
Abstract: A study was carried out to evaluate antimicrobial activity of açaí against Listeria innocua, as a non-pathogenic surrogate for Listeria monocytogenes, at different temperatures (37, 22, and 10 °C), from a kinetic point of view. With this aim, first the Minimum Inhibitory Concentration (MIC) under optimal growth conditions was established (37 °C), and then the effect of 3 non-inhibitory doses (3, 5, and 7 g/L) at 37, 22, and 10 °C was evaluated on the basis of the kinetic parameters lag time ( λ ) and maximum specific growth rate ( μ max ). The Total Phenolic Content (TPC) of the samples tested as a function of açaí concentration was also determined. Results obtained showed that the MIC was 10 g/L, containing 2154.91 ± 126.10 mg of Gallic Acid Equivalents (GAE)/L. At non-inhibitory doses, regardless of temperature, the higher the açaí concentration, the higher the value of λ, and the effect of a variation in açaí concentration on λ was greater at high temperatures. Therefore, the addition of non-inhibitory doses of açaí could provide a means of controlling the growth of L. monocytogenes if a cold chain failure occurs, or if any other reason compromises the microbiological safety of minimally processed foods. Consequently, the present study is important both for the science community and for the food industry because it provides the first mathematical characterization of açaí antimicrobial activity and reveals its potential use to control the concentration and growth of pathogenic bacteria in foods free of non-synthetic additives. Highlights: Açaí antimicrobial effect was mathematically assessed, from a kinetic point of view. The total phenolic content of samples tested was determined spectrophotometrically. Açaí was able to inhibit and slow bacterial growth, in a dose-dependent manner. At non-inhibitory doses, increasing açaí concentration increased lag time. Açaí could be added to minimally processed foods for its preservative potential.